2016
DOI: 10.1021/acs.nanolett.5b05149
|View full text |Cite
|
Sign up to set email alerts
|

Aluminum Nanocrystals as a Plasmonic Photocatalyst for Hydrogen Dissociation

Abstract: Hydrogen dissociation is a critical step in many hydrogenation reactions central to industrial chemical production and pollutant removal. This step typically utilizes the favorable band structure of precious metal catalysts like platinum and palladium to achieve high efficiency under mild conditions. Here we demonstrate that aluminum nanocrystals (Al NCs), when illuminated, can be used as a photocatalyst for hydrogen dissociation at room temperature and atmospheric pressure, despite the high activation barrier… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

8
320
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 309 publications
(329 citation statements)
references
References 52 publications
(77 reference statements)
8
320
1
Order By: Relevance
“…3A, red) closely follows the calculated absorption cross section (black) supporting a hot-carrier mechanism (34). When qualitatively compared with pristine AlNCs, the wavelength dependence of HD production is dramatically different (green), with the maximum HD production occurring at a photoexcitation wavelength of 800 nm, corresponding to the interband transition of Al (15). Quantitative consumption of H 2 at the dipolar LSPR of AlNC:Pd are reported in SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 58%
See 2 more Smart Citations
“…3A, red) closely follows the calculated absorption cross section (black) supporting a hot-carrier mechanism (34). When qualitatively compared with pristine AlNCs, the wavelength dependence of HD production is dramatically different (green), with the maximum HD production occurring at a photoexcitation wavelength of 800 nm, corresponding to the interband transition of Al (15). Quantitative consumption of H 2 at the dipolar LSPR of AlNC:Pd are reported in SI Appendix, Fig.…”
Section: Resultssupporting
confidence: 58%
“…S8. Compared with our previous work, AlNC−Pd antenna−reactor complexes show an order of magnitude greater reactivity than Au/SiO 2 (7) and nearly two orders of magnitude greater reactivity than pristine AlNCs (15). The excitation laser power dependence of this reaction was measured at 492 nm and 800 nm, corresponding to the dipolar plasmon resonance and Al interband transition, respectively, and showed a supralinear response at both wavelengths (Fig.…”
Section: Resultsmentioning
confidence: 51%
See 1 more Smart Citation
“…3 While the design of heterogeneous photocatalysts has focused largely on semiconducting light absorbers, 4,5 it has recently been demonstrated that metallic nanostructures offer unique characteristics for facilitating photocatalytic reactions. [6][7][8][9] Strong light absorption through the excitation of localized surface plasmons on plasmonic metal nanostructures 10 comprised of Au, [11][12][13] Ag, [14][15][16] Cu, 17 or Al, 18 has been shown to drive photocatalytic processes through the excitation and transient transfer of energetic, or hot, carriers to adsorbates. [19][20][21][22][23][24] However, there is limited evidence that the energies of hot carriers in plasmonic nanostructures can be selectively tailored to target specific catalytic reaction pathways, 25,26 and plasmonic nanostructures are optimal catalysts for only a very few 4 relevant industrial chemical processes.…”
Section: Main Textmentioning
confidence: 99%
“…[1][2][3][4][5][6][7] In particular, heterogeneous photocatalysis that couples light with chemical reactions is of paramount importance in chemistry and energy applications. [8][9][10][11][12][13][14][15][16] Plasmonic enhancement is currently a hot topic in catalysis-driven chemistry and photonic materials due to its important role as the main mediator bridging solar energy with other energy forms. For instance, the photocatalytic water splitting reaction used for biomimetic plant photosynthesis represents a promising solution to the growing demands for clean and sustainable energy.…”
Section: Introductionmentioning
confidence: 99%